2011
DOI: 10.3389/fnsys.2011.00084
|View full text |Cite
|
Sign up to set email alerts
|

Map Formation in the Olfactory Bulb by Axon Guidance of Olfactory Neurons

Abstract: The organization of representations in the brain has been observed to locally reflect subspaces of inputs that are relevant to behavioral or perceptual feature combinations, such as in areas receptive to lower and higher-order features in the visual system. The early olfactory system developed highly plastic mechanisms and convergent evidence indicates that projections from primary neurons converge onto the glomerular level of the olfactory bulb (OB) to form a code composed of continuous spatial zones that are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 90 publications
0
11
0
Order By: Relevance
“…Experimental evidence and model studies point toward localized encoding also of behavioral or perceptual aspects in the rat (e.g., Dielenberg and McGregor, 2001; Linster et al, 2001; Kobayakawa et al, 2007; Raman and Gutierrez-Osuna, 2009; Sakano, 2010; Auffarth et al, 2011b). Furthermore, there could be an organizing principle of relative spatial locations of odorant representations, related to chemical similarity (Uchida et al, 2000; Cleland et al, 2002; Johnson et al, 2004), distribution of ORNs on the epithelium (rhinotopy; Miyamichi et al, 2005; Johnson and Leon, 2007), and behavioral relevance.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental evidence and model studies point toward localized encoding also of behavioral or perceptual aspects in the rat (e.g., Dielenberg and McGregor, 2001; Linster et al, 2001; Kobayakawa et al, 2007; Raman and Gutierrez-Osuna, 2009; Sakano, 2010; Auffarth et al, 2011b). Furthermore, there could be an organizing principle of relative spatial locations of odorant representations, related to chemical similarity (Uchida et al, 2000; Cleland et al, 2002; Johnson et al, 2004), distribution of ORNs on the epithelium (rhinotopy; Miyamichi et al, 2005; Johnson and Leon, 2007), and behavioral relevance.…”
Section: Introductionmentioning
confidence: 99%
“…By the simplest model, a measure of ligand similarity and stimulus correlation could serve as the basis for spatial arrangement (e.g. Auffarth et al, 2011c). By this model, odor perception is not the basis of spatial organization, but, on the contrary, would be expected to emerge based on natural stimulus statistics.…”
Section: Discussionmentioning
confidence: 99%
“…In rats, Auffarth et al (2011b) and Raman and Gutierrez-Osuna (2009) found indication that some odor categories can be predicted from spatially clustered areas of glomerular activity patterns and in a subsequent computational model, such a clustering was explained in part by structural similarities of odorants (Auffarth et al, 2011c). In the mice OB, Matsumoto et al (2010) found feature clusters that are associated with odorant categories and behavioral responses.…”
Section: Physiologymentioning
confidence: 99%
See 1 more Smart Citation
“…As Sandoz (2011) shows in his review, the honeybee has been a model for applying behavioral, neurophysiological and neuroanatomical techniques to research on olfactory learning. Two separate models of the role in olfactory learning of the rat olfactory bulb (Auffarth et al, 2011) and the human glomerulus (Schaefer and Margrie, 2012) are presented.…”
mentioning
confidence: 99%